Review Design dalam Rangka Penanggulangan Banjir di Kali Jeroan Kabupaten Madiun - Kurniawan, Andri; Chairunnisa, Nursiah (Lambung Mangkurat University Press, 2024)
Floods occur when the overflowing water cannot be accommodated by the river and inundates the flat area around the river. Flood protection parapets are one method for dealing with flooding on the Jeroan River in Madiun Regency. The 300-meter-long parapet was built in 2019. However, water seepage outside the embankment caused landslides, which was a problem during maintenance. So, from 2020 to 2021, the handling of the Jeroan River is evaluated based on financial conditions and input from the work directors. The stability analysis method was carried out using Geoslope software under normal, earthquake and rapid drawdown conditions. The results of the research were carried out at a location in Gelonggong Village, which was evaluated with three conditions and the addition of simple concrete blocks. The results show the safety factor value for normal conditions is 1.80, earthquake conditions 1.32, and rapid drawdown 1.6. At this location, slope strength is not added because the location is far from residential areas, so it does not endanger residents. The results of the analysis carried out in Kedung Jati Village, where there were three conditions, strengthening gabions and adding flat plate concrete blocks, showed a normal safety factor value of 3.19, earthquake conditions 2.18, and rapid drawdown 3.07. In Warurejo Village, the normal safety factor value was 3.19, earthquake conditions 2.25, and rapid drawdown 3.20. In Babadan Lor Village, the normal safety factor value was 3.26, earthquake conditions 2.78, and rapid drawdown 3.20.